2016
DOI: 10.1016/j.jclinepi.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Missing data in randomized controlled trials testing palliative interventions pose a significant risk of bias and loss of power: a systematic review and meta-analyses

Abstract: ObjectivesTo assess the risk posed by missing data (MD) to the power and validity of trials evaluating palliative interventions.Study Design and SettingA systematic review of MD in published randomized controlled trials (RCTs) of palliative interventions in participants with life-limiting illnesses was conducted, and random-effects meta-analyses and metaregression were performed. CENTRAL, MEDLINE, and EMBASE (2009–2014) were searched with no language restrictions.ResultsOne hundred and eight RCTs representing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 36 publications
2
53
0
Order By: Relevance
“…Looking at our pooled results, there was a higher percentage of dropouts in intervention arm. Hussain et al [37] in a review on missing data in PC RCT reported a similar result with a high dropout rate in intervention arm. However, as we mentioned in results section there was a high level of heterogeneity between studies that didn’t allow to be conclusive in relation to this question.…”
Section: Discussionmentioning
confidence: 79%
“…Looking at our pooled results, there was a higher percentage of dropouts in intervention arm. Hussain et al [37] in a review on missing data in PC RCT reported a similar result with a high dropout rate in intervention arm. However, as we mentioned in results section there was a high level of heterogeneity between studies that didn’t allow to be conclusive in relation to this question.…”
Section: Discussionmentioning
confidence: 79%
“…The trial design was important, and attempts to minimise burden were viewed favourably by participants. This is an important consideration as missing data in trials has been shown to increase with the number of questionnaires/tests [17].…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for attrition included a high symptom burden (21%), patient preference (15%), hospitalisation (10%), and death (6%) [16]. Attrition can lead to high levels of missing data, the level of which, in a recent systematic review of palliative care trials, was associated with study duration and an increasing number of study questionnaires and/or tests [17]. However, even for palliative care drug trials of short duration (4 weeks), attrition has been shown to be high, with only 40% of participants achieving the primary end point in a trial of pregabalin for cancerinduced bone pain [5].…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for attrition included a high symptom burden (21%), patient preference (15%), hospitalisation (10%), and death (6%) (16). Attrition can lead to high levels of missing data, the level of which, in a recent systematic review of palliative care trials, was associated with study duration and an increasing number of study questionnaires and/ or tests (17). However, even for palliative care drug trials of short duration (4 weeks) attrition has been shown to be high, with only 40% of participants achieving the primary end point in a trial of pregabalin for cancer induced bone pain (5).…”
Section: Introductionmentioning
confidence: 99%